Use of Stem Cell Extracellular Vesicles as a “Holistic” Approach to CNS Repair - Branscome, Heather; Paul, Siddhartha; Yin, Dezhong; El-Hage, Nazira; Agbottah, Emmanuel T.; Zadeh, Mohammad Asad; Liotta, Lance A.; Kashanchi, Fatah (Frontiers in Cell and Developmental Biology, 2020)
Neurodegeneration is a hallmark of many diseases and disorders of the central nervous system (CNS). High levels of neuroinflammation are often associated with irreparable damage to CNS cells due to the dysregulation of signaling cascades that are unable to restore a homeostatic balance. Due to the inherent complexity of the CNS, development of CNS-related therapeutics has met limited success. While stem cell therapy has been evaluated in the context of CNS repair, the mechanisms responsible for their functional properties have not been clearly defined. In recent years, there has been growing interest in the use of stem cell extracellular vesicles (EVs) for the treatment of various CNS pathologies as these vesicles are believed to mediate many of the functional effects associated with their donor stem cells. The potency of stem cell EVs is believed to be largely driven by their biological cargo which includes various types of RNAs, proteins, and cytokines. In this review, we describe the characteristic properties of stem cell EVs and summarize their reported neuroprotective and immunomodulatory functions. A special emphasis is placed on the identification of specific biological cargo, including proteins and non-coding RNA molecules, that have been found to be associated with stem cell EVs. Collectively, this review highlights the potential of stem cell EVs as an alternative to traditional stem cell therapy for the repair of cellular damage associated with diverse CNS pathologies.